Gamification in Everyday Classrooms: Observations From Schools in Hong Kong - Lam, Paul; Tse, Alan (Frontiers in Education, 2022)
Gamification refers to the use of game elements in non-game context to improve user experience and engagement (Deterding et. al. 2011). The potential of games to make learning more engaging has been widely noted by educators and researchers. Many of the applications and research studies in this area focused on non-customizable digital games that are designed for a specific group and a narrow range of subject content. In actual classrooms, however, non-customizable digital games may not be flexible enough to enable teachers to adapt gamification into practice. Hence, teachers sometimes use a mixed set of strategies to flexibly embed game-based mechanics into their teaching. How can different gamification tools be applied in classrooms? Based on classroom observations and teacher interviews from schools from primary to secondary level in Hong Kong, this paper explores the role of gamification in real practice. We frame the discussion based on the following approaches with ranging levels of flexibility: versatile gamification, gamification platform, and rigid gamification. Versatile gamification was seen as more feasible compared with the other two approaches We also examine how game-based mechanics such as competition, rules, graphics, and achievements are used to enrich classroom interaction. It was found that gamification is already popular in the classroom. Follow up interviews with teachers suggested that game is a powerful way to engage students. Good practices in game-based lesson design and potentials for further development of gamification tools are discussed.